Study of the Attitude of Users towards Picture Archiving and Communication System Based on the Technology Acceptance Model in Teaching Hospitals of Qom, Iran - Amir Hamta; Maedeh Mohammadzadeh; Maryam Hemati; Marzieh Dehghanzadegan (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2020)
Background and Objectives: Many healthcare providers use health information technology to improve their performance. Picture Archiving and Communication System is a subsystem of the health information system that aims to facilitate the storing, archiving, and managing of digital images as well as their transmission. In this regard, measuring the level of acceptance of technology can be very helpful in the successful implementation of a system. Therefore, the present study aimed to investigate the level of acceptance of Picture Archiving and Communication System by users based on the Technology Acceptance Model questionnaire. This study was conducted in teaching hospitals of Qom, Iran (where the Picture Archiving and Communication System are currently in operation).